2021
DOI: 10.3390/ma14061430
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molybdenum on the Impact Toughness of Heat-Affected Zone in High-Strength Low-Alloy Steel

Abstract: The microstructure, precipitates, and austenite grain in high-strength low-alloy steel were characterized by optical microscope, transmission electron microscope, and laser scanning confocal microscopy to investigate the effect of Mo on the toughness of steel. The microstructure was refined and the toughness was enhanced after the addition of 0.07% Mo in steel. The addition of Mo can suppress the Widmanstätten ferrite (WF) formation and promote the transformation of acicular ferrite (AF), leading to the fine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The samples used for microscopic observation are corroded with 4% nitric acid alcohol. The carbon replica is used to prepare the film, [ 18 ] and the copper mesh is fished and dried for transmission electron microscope observation.…”
Section: Methodsmentioning
confidence: 99%
“…The samples used for microscopic observation are corroded with 4% nitric acid alcohol. The carbon replica is used to prepare the film, [ 18 ] and the copper mesh is fished and dried for transmission electron microscope observation.…”
Section: Methodsmentioning
confidence: 99%
“…It can improve the hardenability of intercritical heat affected zone (ICHAZ), which can deteriorate the impact toughness, although it has been also shown that Mo can improve the HAZ toughness [8]. Wu et al [9] showed that Mo addition can increase the number density of precipitates and also diminished the size of these precipitates, which promoted the refinement of the grain size and the enhancement of the steel toughness in Nb-Mo steel.…”
Section: Introductionmentioning
confidence: 99%